MULTIMEDIA INTEGRATION IN ENGLISH CLASS - Mita Nur Aflah (Jurnal Ilmiah Spectral, 2019)
This study aimed to determine the extent to which multimedia technology can be applied in the process of teaching and learning English and affect student performance. Data obtained from classroom observations and interviews. The analysis shows how the implementation of multimedia or educational applications provides an improvement in the teaching and learning process. The implementation of multimedia particularly educational applications in computer gives students the opportunity to practice using English, as well as increasing students' interest in participating in the classroom activities. In the process of integrating multimedia technologies, the development of the students' skills can be seen. In short, this study shows that the implementation of technology raises a positive impact on students in the learning process in the classroom.